Efektivitas Formula Sediaan Sampo Antijamur Ekstrak Kulit Pisang Kepok (Musa paradisiaca L.) Terhadap Pertumbuhan Malassezia furfur - Maria Vianey Dominika Seda Pia; Prisca Deviani Pakan; Iswa Ningsih; Desi Indriarini (Cendana Medical Journal, 2026)
Abstract Background: Malassezia furfur is a pathogenic organism that causes dandruff. One way to prevent dandruff is by washing the hair using shampoo that contains anti-dandruff active ingredients. Continuous use of synthetic shampoos can cause the hair to become dry, easily brittle, irritate the eyes and scalp, and damage the hair shaft. Herbal shampoos have become popular due to consumers’ belief that they contain natural ingredients that are safer and have minimal side effects. One natural ingredient that can be used is the peel of kepok banana (Musa paradisiaca L.). Objective: To determine the antifungal activity of a shampoo formulation containing kepok banana peel extract (Musa paradisiaca L.) against the growth of Malassezia furfur. Methods: The type of research conducted was a true experimental study with a post-test only control group design. In this study, there were treatment groups given shampoo containing kepok banana peel extract at concentrations of 1.56%, 3.125%, 6.25%, 12.5%, 25%, 50%, and 100%, a negative control group using the shampoo base, and a positive control group using shampoo containing 1% selenium sulfide. The data were analyzed using One-Way ANOVA. Results: All shampoo formulations showed suboptimal physical characteristics. Concentrations of 6.25%, 12.5%, 25%, 50%, and 100% demonstrated antifungal activity against the growth of Malassezia furfur. Conclusion: There is antifungal activity from the shampoo formulation containing kepok banana peel extract (Musa paradisiaca L.) against the growth of Malassezia furfur.